Personally addressed hand-signed letters increase questionnaire response: a meta-analysis of randomised controlled trials - Edwards Phil; Scott Pippa (BMC Health Services Research, 2006)
Abstract Background Postal questionnaires are commonly used to collect data for health studies, but non-response reduces study sample sizes and can introduce bias. Finding ways to increase the proportion of questionnaires returned would improve research quality. We sought to quantify the effect on response when researchers address participants personally by name on letters that accompany questionnaires. Methods All randomised controlled trials in a published systematic review that evaluated the effect on response of including participants' names on letters that accompany questionnaires were included. Odds ratios for response were pooled in a random effects meta-analysis and evidence for changes in effects over time was assessed using random effects meta-regression. Results Fourteen randomised controlled trials were included covering a wide range of topics. Most topics were unrelated to health or social care. The odds of response when including participants' names on letters were increased by one-fifth (pooled OR 1.18, 95% CI 1.03 to 1.34; p = 0.015). When participants' names and hand-written signatures were used in combination, the effect was a more substantial increase in response (OR 1.45, 95% CI 1.27 to 1.66; p < 0.001), corresponding to an absolute increase in the proportion of questionnaires returned of between 4% and 10%, depending on the baseline response rate. There was no evidence that the magnitude of these effects had declined over time. Conclusion This meta-analysis of the best available evidence indicates that researchers using postal questionnaires can increase response by addressing participants by name on cover letters. The effect appears to be enhanced by including hand-written signatures.